Dogma, Tradition, Historicity: Contribution of Yves Congar and Bernard Lonergan - Kristiatmo, Thomas (Media: Jurnal Filsafat dan Teologi, 2025)
The inquiry into the understanding of dogmas has been prompted by historical consciousness. Dogmas were traditionally viewed as universal and a-historical until historical consciousness emerged, leading to the questioning of their truth claims. Some attempted to rely on common sense, but this proved futile. To provide a more nuanced solution to the issue of determining the truth claims of dogma, the author introduces the ideas of Yves Congar and Bernard Lonergan. Through the method of dialectic, this study aims to explore Congar's concept of living tradition and Lonergan's distinction between the permanence and historicity of dogma. This investigation seeks to resolve the tension between what is permanent and what is historical, which primarily arises from different levels of consciousness.